EFEK MAKRO EKONOMI DAN ISLAMIC PHILANTROPY TERHADAP PERTUMBUHAN EKONOMI - Bayu Nurhadi (Elastisitas : Jurnal Ekonomi Pembangunan, 2024)
This research aims to determine the role of macroeconomic effects and Islamic philanthropy on economic growth in Indonesia. Because the data used is time series data, a much more specific model is needed, so an ECM (Error Correction Model) is used to determine the long-term and short-term impacts. Quantitative methods are used for data analysis with the help of Eviews 12. The data used is secondary data from 1995 - 2022. The research results show that FDI and Zakat affect positive and significantly to economic growth both short- and long-term way. On the other hand, foreign debt and inflation affect negative and significant to economic growth in short term, while in the long term both foreign debt and inflation affect negative but insignificant to economic growth.